THE INFLUENCE OF DEBIT CARDS AND ELECTRONIC MONEY ON SPENDING HABITS OF STUDENTS AT MUHAMMADIYAH UNIVERSITY OF SIDOARJO - Rosafi, Muhammad Amrullah; Harianto, Wiwit (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to determine the effect of debit cards and electronic money on students' spending habits. Method: This research took place at the Muhammadiyah University of Sidoarjo and was conducted by distributing questionnaires to 81 active students of the Muhammadiyah University of Sidoarjo as respondents. In this study, the analysis used was multiple linear regression and the tool used to conduct the analysis was SPSS. The data used for the analysis was primary data obtained from 81 respondents. Results: Based on the results of this study, it can be seen that debit cards and electronic money have a significant influence on the spending habits of students at the Muhammadiyah University of Sidoarjo. Novelty: This research is motivated by the increasing use of debit cards and electronic money in transactions. The series of advantages possessed by these two payment instrument innovations make their users use them more often to make transactions.